Is student mentoring career-defining in surgical disciplines? A comparative survey among medical schools and medical students for mentoring programs - Hertling, Stefan Ferdinand; Back, David Alexander; Wildemann, Britt; Schleußner, Ekkehard; Kaiser, Mario; Graul, Isabel (Frontiers in Medicine, 2022)
Objective Facing a shortage of young surgeons, this study aimed to examine the availability of mentoring programs and if this can counteract this lack. Summary background data Medical mentoring programs have proven to be decisive to influence students’ later career decisions. Since their structure may depend on the medical school and the effort of single disciplines, the offers are often very heterogeneous. Methods Anonymous online-questionnaires were developed and distributed among medical students in Germany and the dean for teaching of the medical schools from July 2019 to January 2020 in Germany. Data of the availability of mentoring programs, their structure and the impact of surgery were collected. Results Forty three medical schools participated, with 65% offering mentoring programs. 18 of medical schools had no additional funding available for this. Surgical subjects participated in these programs in only 30%. Additionally, 1,516 medical students participated in the second survey. A total of 70% had already participated in a mentoring program with a significantly higher proportion of men. Of these, 94% stated that this was helpful and had an impact on their career planning, without any gender differences. 95% would participate in structured surgical mentoring programs and 95% agreed that this could have an impact on their career planning. Conclusion Mentoring programs may be able to influence career planning, nevertheless participation by surgical specialties has been low. Becoming more active in providing mentoring programs with a special focus on women and offering more surgical content can be a way to counteract the lack of surgical trainees.